Tikhonov regularization method for a system of equilibrium problems in Banach spaces - Dang, Thi Hai Ha; Nguen, Byong (Ukrains’kyi Matematychnyi Zhurnal, 2009)
The purpose of this paper is to investigate the Tikhonov regularization method for solving a system of ill-posed equilibrium problems in Banach spaces with a posteriori regularization-parameter choice. An application to convex minimization problems with coupled constraints is also given.